Side effects during subcutaneous immunotherapy in children with allergic diseases. Issue 3 (17th January 2018) - Tophof, Max A.; Hermanns, Anne; Adelt, Thomas; Eberle, Peter; Gronke, Christine; Friedrichs, Frank; Knecht, Roland; Mönter, Ernst; Schöpfer, Helmut; Schwerk, Nicolaus; Steinbach, Jörg; Umpfenbach, Hans‐Ulrich; et al.
Abstract: Background: Allergen‐specific immunotherapy is the only causal form of therapy for IgE‐mediated allergic diseases. Subcutaneous immunotherapy (SCIT) is considered safe and well tolerated in adults, yet there is less evidence of safety in the pediatric population. Methods: A non‐interventional prospective observing longitudinal study was carried out to determine the incidence of local and systemic side effects by SCIT, routinely performed in pediatric patients. A total of 581 pediatric patients were observed in 18 study centers between March 2012 and October 2014, recording 8640 treatments and 10 015 injections. Results: A total of 54.6% of the patients experienced immediate local side effects at least once; delayed local side effects were seen in 56.1%. Immediate systemic adverse reactions occurred in 2.2% of patients; 7.4% experienced delayed systemic side effects. However, severe systemic side effects (grade III in the classification of Ring and Messmer) were seen in 0.03% of all treatments, all appearing within 30 minutes after the injections. No grade IV reactions were observed. In addition, many potential risk factors were investigated, yet only a few were found to be associated with the occurrence of side effects. Conclusions: Subcutaneous immunotherapy is a safe form of therapy in pediatric patients, with similar rates of local side effects compared to adult patients and low rates of severe systemic side effects. However, local and systemic reactions occurring later than 30 minutes after injection were observed more often than expected, which makes it essential to be attentive on behalf of pediatricians, patients, and parents.